Comparison of two porcine benign esophageal stricture models using radiofrequency ablation and endoscopic submucosal tunnel dissection - Bang, Byoung Wook; Jeong, Seok; Lee, Don Haeng (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Large-animal benign esophageal stricture (BES) models are needed for the development of new endoscopic therapies and related devices. This study was undertaken to develop and compare swine BES models produced by radiofrequency ablation (RFA) or endoscopic submucosal tunnel dissection (ESTD). Materials and Methods: RFA and ESTD were each performed on three pigs. Follow-up endoscopy and esophagography were performed immediately after the procedures and then 2, 3, and 4 weeks later. Four weeks after the procedures, all animals were sacrificed, and gross and histologic examinations were performed. Results: BES was successfully achieved in both the RFA and ESTD groups, and all animals survived without any serious adverse events during the 4-week follow-up period. Mean procedural times were 9.3 min for RFA and 89.3 min for ESTD. ESTD caused long segment strictures whose average length was 4.5 cm, whereas RFA produced short strictures whose average length was 1.4 cm. BES began to form 2 weeks after both procedures. Degrees of strictures were similar at 3 and 4 weeks in the ESTD group; however, it started deteriorating over time in the RFA group. Histologic examinations showed that ESTD caused inflammation and fibrosis in the submucosal layer, whereas RFA induced extensive inflammation in the submucosal and muscularis propria layers. Conclusion: BES was successfully achieved using RFA or ESTD in swine without serious complications. The methods have different characteristics; therefore, researchers should choose the method more appropriate for their purposes. Cite this article as: Bang BW, Jeong S, Lee DH. Comparison of two porcine benign esophageal stricture models produced by radiofrequency ablation and endoscopic submucosal tunnel dissection. Turk J Gastroenterol 2018; 29: 502-8.